Labview-Based Image Processing Enabling Induction Motor Fault Finding - Burange, Rahul (Journal of Power Electronics and Devices, 2023)
This research addresses the imperative need for advanced fault detection methodologies in induction motors, crucial components in industrial applications. Traditional fault detection techniques often rely on sensor-based approaches, facing limitations in certain scenarios. This study proposes an innovative solution utilizing LabVIEW-based image processing for non-intrusive fault finding in induction motors. The system captures visual data and employs advanced image processing algorithms, coupled with machine learning, to enhance fault detection capabilities. The objective is to provide a real-time, efficient, and non-intrusive method for identifying various faults in induction motors, thus contributing to the reliability and operational efficiency of industrial systems.